2021
DOI: 10.1038/s41408-021-00541-0
|View full text |Cite
|
Sign up to set email alerts
|

ASXL1 mutations are associated with distinct epigenomic alterations that lead to sensitivity to venetoclax and azacytidine

Abstract: The BCL2-inhibitor, Venetoclax (VEN), has shown significant anti-leukemic efficacy in combination with the DNMT-inhibitor, Azacytidine (AZA). To explore the mechanisms underlying the selective sensitivity of mutant leukemia cells to VEN and AZA, we used cell-based isogenic models containing a common leukemia-associated mutation in the epigenetic regulator ASXL1. KBM5 cells with CRISPR/Cas9-mediated correction of the ASXL1G710X mutation showed reduced leukemic growth, increased myeloid differentiation, and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…Leukemic cells with ASXL1 mutation have been shown to overexpress anti-apoptotic Bcl-2 and have increased global cytosine methylation levels. It is not surprising that these cells were sensitive to both the Bcl-2 inhibitor venetoclax and the DNMT-inhibitor azacytidine [258]. In addition, clinical trials have shown the efficacy of venetoclax combined with hypomethylating agents or low-dose cytarabine in a subgroup of AML patients [259].…”
Section: Additional Sex Like Comb Protein 1 (Asxl1)mentioning
confidence: 99%
“…Leukemic cells with ASXL1 mutation have been shown to overexpress anti-apoptotic Bcl-2 and have increased global cytosine methylation levels. It is not surprising that these cells were sensitive to both the Bcl-2 inhibitor venetoclax and the DNMT-inhibitor azacytidine [258]. In addition, clinical trials have shown the efficacy of venetoclax combined with hypomethylating agents or low-dose cytarabine in a subgroup of AML patients [259].…”
Section: Additional Sex Like Comb Protein 1 (Asxl1)mentioning
confidence: 99%
“…ASXL1 mutation was recently found to drive response to Venetoclax in vitro . ASXL1 acts as an epigenetic regulator via PRC2-mediated chromatin modification to keep various genes in a repressed state [ 34 ] . Thus, ASXL1 mutation leads to aberrant activation of its target genes, including BCL2 [ 34 ] .…”
Section: Mechanism Of Action Of Venetoclaxmentioning
confidence: 99%
“…ASXL1 acts as an epigenetic regulator via PRC2-mediated chromatin modification to keep various genes in a repressed state [ 34 ] . Thus, ASXL1 mutation leads to aberrant activation of its target genes, including BCL2 [ 34 ] . In preclinical study of Rahmani et al .…”
Section: Mechanism Of Action Of Venetoclaxmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 However, the clone composition may impact on the probability of response and its duration. 5 6 Patients with AML and NPM1 and/or IDH2 mutations have the highest probability of response to VEN/HMA combinations, but also RUNX1 mutations appear to be associated with favorable responses. On the other hand, activating kinase mutations such as FLT3-ITD , N/KRAS , CBL , or KIT have been associated with treatment resistance.…”
Section: Introductionmentioning
confidence: 99%